Methods for assessing the effectiveness of treatment using klotho protein and fibroblast growth factor 23 in patients with renal dysfunction - Nilufar Gadaeva (International Journal of Medical Science and Public Health Research, 2025)
Chronic kidney disease (CKD) is a progressive condition that disrupts mineral metabolism, leading to complications such as vascular calcification, cardiovascular disease, and impaired phosphate regulation. Klotho protein and fibroblast growth factor 23 (FGF23) are essential biomarkers involved in these processes, making them valuable indicators for assessing the efficacy of therapeutic interventions. This review explores various methodologies for evaluating treatment outcomes in CKD patients, including biochemical assays, molecular analyses, imaging techniques, and functional assessments. The integration of these approaches enhances our ability to monitor disease progression and optimize patient management strategies.